Biopesticidal Potential of Lippia javanica (Burm. F) Spreng. Leaf Extracts and their Fractions against Spodoptera litura (Fab.) - Pavunraj, M.; Ezhumalai, P.; Nagarajan, K.; Murali, P.; Rajeshkumar, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Three organic solvent extracts of Lippia javanica leaves were screened for their antifeedant and larvicidal activities against the 4th instar larvae of Spodoptera litura at 5% concentration. The maximum antifeedant and larvicidal activities were recorded in ethyl acetate extract (76.57%) for antifeedant and (90.40%) for larvicidal activity, followed by chloroform and hexane extracts. Ten fractions were obtained from the ethyl acetate extract of L. javanica by using different combinations of hexane and ethyl acetate as the mobile phase through column chromatography. The fractions were screened at 1000 ppm concentrations for antifeedant and larvicidal activities. Fraction 10 (71.75%) was found to be the most effective one, followed by fraction 4 (61.32%) and fraction 7 (60.58%) for antifeedant acitivity. At a 1000 ppm concentration, fraction 3 exhibited the highest larvicidal activity (79.20%) against S. litura, followed by fraction 1 (76.0%), while fractions 5 and 6 have shown equal activity. Quantitative protein analysis revealed that treatment with the eighth fraction reduced the haemolymph protein drastically (1.52 mg/mL) compared to control (2.84 mg/mL) and other fractions. In the reference control azadirachtin treatment, the haemolymph protein quantity was found to be nearly the same (1.4 mg/mL) as that of the eighth fraction. Treatment with the first and second fractions resulted in increased haemolymph protein (8 and 7.6 mg/mL, respectively). The bio-efficacy of L. javanica in pest management is discussed.